The Role of Social Media Marketing Activities on Customer Equity Drivers and Customer Loyalty - Vika Ansy Anggraini; Arga Hananto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
During the past few years, adoption of e-commerce in Indonesia has been increasing along with other trends in information , communication and technology sector such as widespread use of smartphones and social media. To promote its services, e-commerce firms have also embraced social media and carry out social media marketing activities. This study is aimed to test the influence of social media marketing activities toward customer loyalty through customer equity drivers (i.e. Value Equity, Brand Equity, dan Relationship Equity.). A survey was conducted using convenience sampling technique to select respondents. A total of 161 usable responses were used in the main data analysis. This study found support for the five dimensions of social media marketing activities suggested from previous study. Furthermore, this study found that social media marketing activities affect value equity, brand equity and relationship equity. This study also found that two customer equity drivers (brand equity and relationship equity)had a positive effect on customer loyalty, while value equity had a positive effect on customer loyalty, but it was not significant. Discussion and managerial implications were also discussed in this study